2022
DOI: 10.1007/jhep02(2022)030
|View full text |Cite
|
Sign up to set email alerts
|

Off-shell Higgs production at the LHC as a probe of the trilinear Higgs coupling

Abstract: In the context of the Standard Model effective field theory (SMEFT) we examine the constraints on the trilinear Higgs coupling that originate from off-shell Higgs production in proton-proton collisions. Our calculation of the gg → h* → ZZ → 4ℓ process includes two-loop corrections to gluon-gluon-fusion Higgs production and one-loop corrections to the Higgs propagator and its decay. Employing a matrix-element based kinematic discriminant we determine the reach of LHC Run 3 and the high-luminosity option of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Being sensitive not only to m 4 but also to another seven variables such as the invariant masses of the two opposite-sign lepton pairs (for details consult the articles [41][42][43]), ME-based discriminants fully exploit the event kinematics. As in our recent study [44], we find that the use of a ME method leads to a significantly improved coverage of the BSM parameter space, i.e. c φ and m φ in the case of (1.1), than a shape analysis of the m 4 distribution.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Being sensitive not only to m 4 but also to another seven variables such as the invariant masses of the two opposite-sign lepton pairs (for details consult the articles [41][42][43]), ME-based discriminants fully exploit the event kinematics. As in our recent study [44], we find that the use of a ME method leads to a significantly improved coverage of the BSM parameter space, i.e. c φ and m φ in the case of (1.1), than a shape analysis of the m 4 distribution.…”
Section: Introductionsupporting
confidence: 82%
“…Notice that (3.2) is accurate in the case of the m 4 spectrum. For the D S distribution one observes [44] a close to flat K-factor of around 1.6 between the LO and the improved prediction (3.2). It is furthermore found that the inclusion of higher-order QCD corrections reduces the scale uncertainties by a factor of about 3 from…”
Section: Me-based Kinematic Discriminantmentioning
confidence: 73%
See 2 more Smart Citations
“…Recently, off-shell Higgs decay H * → Z * Z * → 4 leptons have been measured at the LHC in [3,4,5,6,7,8]. We also can find many interesting points from the phenomenological studies for off-shell Higgs decays in [9,10,11,12,14,15,16,17,18,19,20]. In all mentioned references, the authors have not only provided the framework for testing the Higgs scalar sector at different energy scales but also discussed the possibility to explore new physics beyond the SM (BSM).…”
Section: Introductionmentioning
confidence: 95%